The Refugee Problem: Statement Submitted by the Inter-Parliamentary Union - Héderváry, Claire de (1958)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): United Nations. Economic and Social Counsel The recommendations concerning the Protocol to facilitate housing, employment, movement and repatriation of refugees and their families.